Revisitando os verbos em Parkatêjê: questões relevantes para um estudo morfossintático - FREITAS, Marília Fernanda Pereira de (2008)
This work named Revisitando os Verbos em Parkatêjê: questões relevantes para um estudo morfossintático aims to show some of the principal characteristics of verbs in Parkatêjê language. Parkatêjê community lives in Km 30 of BR-222 highway, in Mãe Maria Village, Bom Jesus do Tocantins. This study was made up through bibliographical research, having as foundation Ferreira (2003), including her own data and data of Araújo (in different moments of her study). This theme was chosen because there is few linguistic descriptive works about Parkatêjê language. In a first moment, it will be presented some definitions about verb, according to Payne (1997), Lyons (1979), Schachter (1985), Lehmann (1981) and Givón (1984); after that, according to Rodrigues (1999) and Ribeiro (2006), the principal characteristics of Macro-Jê languages will be showed. The main characteristics of Parkatêjê language, according to Ferreira (2003), will be presented, with special attention to verbs.